The Impact of Insurer Financial Health and Market Discipline on Life Insurance Demand: A Case Study of Indonesia - Kristio Rapi; Dominicus Savio Priyarsono; Siti Jahroh; Toni Bakhtiar (School of Business, Bogor Agricultural University (SB-IPB), 2026)
Background: The life insurance industry in Indonesia has faced